2010
DOI: 10.2478/s11534-009-0126-5
|View full text |Cite
|
Sign up to set email alerts
|

Coupled tensorial form for atomic relativistic two-particle operator given in second quantization representation

Abstract: Abstract:General formulas of the two-electron operator representing either atomic or effective interactions are given in a coupled tensorial form in relativistic approximation. The alternatives of using uncoupled, coupled and antisymmetric two-electron wave functions in constructing coupled tensorial form of the operator are studied. The second quantization technique is used.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The phase multiplier Υ is optional. Usually it is chosen to be equal to 15 In general, the two-particle interaction operator g 12 acts on H × H. However, g γ is reduced and it acts on irreducible tensor space H γ , obtained by reducing 25 (Sec. 2, Eq.…”
Section: The Third-order Effective Hamiltonianmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase multiplier Υ is optional. Usually it is chosen to be equal to 15 In general, the two-particle interaction operator g 12 acts on H × H. However, g γ is reduced and it acts on irreducible tensor space H γ , obtained by reducing 25 (Sec. 2, Eq.…”
Section: The Third-order Effective Hamiltonianmentioning
confidence: 99%
“…In Ref. 25 , it was showed that v μαζ β may be constructed in two distinct ways: (i) reducing the Kronecker product (…”
Section: The Third-order Effective Hamiltonianmentioning
confidence: 99%
“…In MBPT this coefficient denotes miscellaneous products of one-or two-particle matrix elements (with energy denominator included). The systematic study of two-particle matrix elements can be found in [12][13][14]. The application of this methodology for the second-order effective Hamiltonian one can find in [15].…”
Section: Introductionmentioning
confidence: 99%